A Psycholinguistic Analysis on Speech Errors Made by Kamala Harris - Annisa, Ratu; Sembiring, Matius Cikepen Annalela; Perangin-Angin, Alemina Br. (Politeknik Harapan Bangsa Surakarta, 2022)
This article entitled A Psycholinguistic Analysis on Speech Errors Made by Kamala Harris. The purpose of this study is to find out the types and the causes of speech errors made by Kamala Harris at the Debate of the Candidates for Vice President of America. The design of this research was qualitative design. The data were in the form of words, phrases, and sentences that contain speech errors. The data were taken by running a YouTube. The data were collected through stages: finding out and determining, classifying, and separating the words, phrases, and sentences that contain speech errors made by Kamala Harris. Analysis of data qualitatively using the analysis phase of Miles, Huberman, and Saldana: condensation, display, and verification.Â The research result shows the types of speech errors made by Kamala Harris based on Clark & Clarkâ€™s theory found are: silent pause 25 times, filled pause 27 times, repeats 21 times, retraced false starts 1 time, unretraced false starts 1 time, correction 2 times, stutter 2 times and interjection 2 times. There is no slip of the tongue. The causes of speech errors made by Kamala Harris are social factors both situational anxiety and social circumstances